Orphans, doubling, coordination, and phases - Franks, Steven (Slovenski jezik, 2013)
This contribution examines the Orphan Accusative (OA) construction found in Slovenian with the aim of understanding its unique properties within an articulated model of noun phrase structure.
Keywords: grammar; navezovalni tožolnik; noun phrase structure; orphan accusative; Slovene; Slovene language; slovenščina; slovnica